Design of Proposed Opening of Onamazu Farm Business Branch in Coblong District Bandung West Java - Muhammad Tariq Arrazzaq; Maria Dellarosawati Idawicaksakti; Isnaeni Yuli Arini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Onamazu Farm is a company engaged in catfish farming. The product sold by Onamazu Farm is consumption catfish with a size of 110-120gr/head or the equivalent of 7-8 fish per Kg. Onamazu Farm was established in 2018, until now Onamazu Farm can produce around 1,000 Kg of catfish in each period. From the demand data for the past 3 years, a problem was found where the company was unable to meet market demand. From the fishbone analysis, it is known that the main problem lies in the poor facilities and limited land owned. So that the opening of the Onamazu Farm branch by reviewing market, technical and financial aspects is considered to be able to solve the problems being faced. This research uses linear trend forecasting method, single exponential smoothing and moving average. The method with the smallest MSE will be chosen to obtain market aspect data. Furthermore, the straight-line depreciation method is used to obtain the depreciation value on the technical aspects. In the financial aspect, several methods are used such as internal rate of return (IRR), net present value (NPV), and payback period (BPB) to determine whether the business design is feasible or not.